N-Acetyldopamine Dimer Attenuates DSS-Induced Ulcerative Colitis by Suppressing NF-κB and MAPK Pathways - Huang, Li-Jun; Wang, Yu-Mei; Gong, Lei-Qiang; Hu, Chao; Gui, Yu; Zhang, Chen; Tan, Xue; Yu, Xian-Kuo; Liao, Yi-Le; Luo, Yan; Tang, Yu-Qin; Dai, Yi-Fei; et al. (Frontiers in Pharmacology, 2022)
Ulcerative Colitis (UC) is a major form of chronic inflammatory bowel disease of the colonic mucosa and exhibits progressive morbidity. There is still a substantial need of small molecules with greater efficacy and safety for UC treatment. Here, we report a N-acetyldopamine dimer (NADD) elucidated (2R,3S)-2-(3’,4’-dihydroxyphenyl)-3-acetylamino-7-(N-acetyl-2’’-aminoethyl)-1,4-benzodioxane, which is derived from traditional Chinese medicine Isaria cicadae, exhibits significant therapeutic efficacy against dextran sulfate sodium (DSS)-induced UC. Functionally, NADD treatment effectively relieves UC symptoms, including weight loss, colon length shortening, colonic tissue damage and expression of pro-inflammatory factors in pre-clinical models. Mechanistically, NADD treatment significantly inhibits the expression of genes in inflammation related NF-κB and MAPK signaling pathways by transcriptome analysis and western blot, which indicates that NADD inhibits the inflammation in UC might through these two pathways. Overall, this study identifies an effective small molecule for UC therapy.